Proximity-driven acceleration of challenging solid-phase peptide couplings - Joshua Parker; Brooke A. Farrell; Karlee A. Kohuth; Landon Parker; Skander A. Abboud; Thomas Kodadek (Proceedings of the National Academy of Sciences, 2026)
Many important solid-phase synthesis reactions proceed slowly and inefficiently, for example, the coupling of an activated ester to a sterically hindered, bead-displayed amine, a critical step in the synthesis of many peptides. Forcing conditions are often required to achieve acceptable yields. We show here that such reactions can be accelerated by tethering to the bead a nucleophilic pyridine catalyst, which reacts with the activated ester, creating a high local concentration of a reactive acylpyridinium intermediate that couples efficiently to the bead-displayed amine. In many cases, the “cleanliness” of reactions carried out on resins equipped with an immobilized catalyst is substantially better than the analogous reactions in which the catalyst is added to the solution.